Efeito de diferentes estratégias de restauração sobre o estoque de carbono na amazônia maranhense - Paixão, Larissa Rebeca Rego Santos (2019)
Biodiversity ecological restoration systems may be important carbon sinks contributing to climate change mitigation. This research aimed to evaluate three methods of ecological restoration of degraded areas (natural regeneration, nucleation and agroforestry system / SAF) six years after its implementation. The experimental area was delineated by 18 permanent plots of 900 m2, inserted in 6 blocks with 3 treatments, where vegetation (trees, bushes, vines, herbaceous and palm trees), necromass (litter, branches and dead trees) and soil (0-10 and 10- 20cm) were sampled. Biomass was estimated using allometric models (vegetation with DAP> 1cm and dead trees) and destructively (herbaceous, burlap and thin branches). The increase in total carbon stock was higher in agroforestry system (37,4 ± 22,1 t C ha-1) followed by nucleation (20,6 ± 9,3 t C ha-1) and natural regeneration (13,4 ± 3,4 t C ha-1). Above-ground living biomass (BVAS) was the component that most contributed to the total carbon stock in agroforestry system (70 ± 15%) and in nucleation systems (67 ± 14%), while in natural regeneration the soil organic carbon stood out (47 ± 22%). Regarding the components that integrates the BVAS, trees (DAP>10cm) had a greater participation in agroforestry system treatments (47 ± 25%) and nucleation (39 ± 31%), mainly due to the trees planted, while in natural regeneration stood out palm trees (47 ± 34%). The fixed carbon is strongly correlated with the abundance, richness and diversity of planted trees. The adoption of these active restoration strategies in agricultural activities can provide the farmer with economic benefits, allow the environmental regularization of rural properties, and restore vital ecosystem services, such as carbon sequestration, contributing to Brazil's international restoration commitments.